Video broadcast using cloud computing with metadata (International Journal of Engineering and Computer Science, 2017)
-   In this paper the model of broadcast digital video signal with embedded audio (SDI) using cloud computing is detailed in each transcoding process of the signal. The SDI signal is coding and multiplexing in ASI signal, Multidecriptor transcoding the signal in Transport Stream, with GT-3 we can change the program in a new TS. Then with CPC develop chuncks with HLS (Http live streaming), with diferents profile. Anevia recive this chunck and delivery the signal to cloud. Testing bandwidth and bit rate for each signal process is performed, without losing the quality control standards and without losing the services of metadata (V-chip, closed caption, cue tone, DPI, GPI, Watermarket, SCTE 35 y104, etc.). How the stream is received by the end user it is shown.